The Influence of Resin Infiltration on the Shear Bond Strength of Orthodontic Brackets: A Systematic Review and Meta-Analysis - Sylwia Kiryk; Jan Kiryk; Jacek Matys; Maciej Dobrzyński (Journal of Functional Biomaterials)
The quality of the enamel plays a critical role in the retention and performance of orthodontic brackets. This systematic review and meta-analysis aimed to evaluate the effect of resin infiltration pretreatment on the shear bond strength (SBS) of orthodontic brackets. An electronic search was conducted in October 2024 using PubMed, Web of Science (WoS), and Scopus databases, employing the keywords (resin infiltration AND bracket); (ICON AND bracket). The review adhered to PRISMA guidelines and utilized the PICO framework. Of the 143 articles initially identified, 63 underwent screening. Strict inclusion criteria were applied of which the most important were resin infiltration pretreatment, studies conducted on natural teeth and SBS evaluation. This left 19 studies for final analysis. The risk of bias was assessed using the checklist for quasi-experimental studies (Non-Randomized Experimental Studies) developed by the Joanna Briggs Institute (JBI). Among these, 13 studies used human teeth and 13 utilized Transbond XT as the adhesive. Metal brackets were predominantly examined (n = 17). The Adhesive Remnant Index (ARI) was assessed in 13 studies. Importantly, 11 studies concluded that resin infiltration significantly enhances SBS, 8 of which were conducted on human teeth. The meta-analysis revealed significantly higher SBS results when resin infiltrate was applied to healthy enamel. This finding underscores the dual benefits of resin infiltration: increased bond strength and the protection of enamel integrity during debonding procedures. The results suggest that resin infiltration not only improves the mechanical retention of orthodontic brackets but also serves as an enamel-preserving approach.